Donor information based prediction of early allograft dysfunction and outcome in liver transplantation. (24th January 2014) - Hoyer, Dieter P.; Paul, Andreas; Gallinat, Anja; Molmenti, Ernesto P.; Reinhardt, Renate; Minor, Thomas; Saner, Fuat H.; Canbay, Ali; Treckmann, Jürgen W.; Sotiropoulos, Georgios C.; Mathé, Zoltan
Abstract Background & Aims Poor initial graft function was recently newly defined as early allograft dysfunction (EAD) [Olthoff KM, Kulik L, Samstein B, et al. Validation of a current definition of early allograft dysfunction in liver transplant recipients and analysis of risk factors. Liver Transpl 2010; 16: 943]. Aim of this analysis was to evaluate predictive donor information for development of EAD. Methods Six hundred and seventy‐eight consecutive adult patients (mean age 51.6 years; 60.3% men) who received a primary liver transplantation (LT) (09/2003–12/2011) were included. Standard donor data were correlated with EAD and outcome by univariable/multivariable logistic regression and Cox proportional hazards to identify prognostic donor factors after adjustment for recipient confounders. Estimates of relevant factors were utilized for construction of a new continuous risk index to develop EAD. Results 38.7% patients developed EAD. 30‐day survival of grafts with and without EAD was 59.8% and 89.7% (P < 0.0001). 30‐day survival of patients with and without EAD was 68.5% and 93.1% (P < 0.0001) respectively. Donor body mass index (P = 0.0112), gGT (P = 0.0471), macrosteatosis (P = 0.0006) and cold ischaemia time (CIT) (P = 0.0031) were predictors of EAD. Internal cross validation showed a high predictive value (c‐index = 0.622). Conclusions Early allograft dysfunction correlates with early results of LT and can be predicted by donor data only. The newly introduced risk index potentially optimizes individual decisions to accept/decline high risk organs. Outcome of these organs might be improved by shortening CIT.